Pemberian Kapur Pertanian Untuk Meningkatkan pH Tanah di Desa Tanjung Sari, Kabupaten OKU - Novriani, Novriani; Pusvita, Ema; Asroh, Ardi; Gribaldi, Gribaldi; Nurlaili, Nurlaili; Danial, Ekawati; Yulhasmir, Yulhasmir; Diana, Susanti; Dewi, Nurmala; Sakalena, Firnawati; Fatmanurshanti, Dora; Lastinawati, Endang; Rosmawati, Henny; Ogari, Putri Ayu; Lestari, Windi (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Acidic soils are one of the major constraints in agricultural development in tropical regions, including in Tanjung Sari Village, Ogan Komering Ulu (OKU) Regency. Field surveys indicated that most farmlands in this village have soil pH ranging from 4.5 to 5.0, which is categorized as acidic. This condition negatively affects nutrient availability, microbial activity, and the productivity of food and horticultural crops. One of the recommended practices to overcome this problem is the application of agricultural lime (liming). This activity aimed to improve farmers’ knowledge and skills regarding the benefits, dosage, and techniques of lime application, as well as to directly improve soil pH through field demonstration. The method consisted of three stages: preparation (survey and soil analysis), implementation (training, extension, and field practice), and evaluation (measurement of soil pH and assessment of farmers’ knowledge improvement). The training materials included soil pH concepts, its influence on crop growth, types of agricultural lime, calculation of lime requirements, and proper application techniques. The results of this activity indicated an increase in farmers’ understanding of the importance of liming and an improvement in soil pH in demonstration plots after lime application. In conclusion, liming practices in Tanjung Sari Village proved beneficial for improving soil quality and supporting sustainable agricultural productivity. It is expected that farmers will be able to apply this technology independently in the future, with continuous support from local government through the provision of agricultural lime.ABSTRAKTanah masam merupakan salah satu kendala utama dalam pengembangan pertanian di daerah tropis, termasuk di Desa Tanjung Sari, Kabupaten Ogan Komering Ulu (OKU). Hasil survei menunjukkan bahwa sebagian besar lahan pertanian di desa ini memiliki pH tanah berkisar antara 4,5–5,0, yang tergolong masam dan berdampak negatif terhadap penyerapan unsur hara, aktivitas mikroorganisme, serta produktivitas tanaman pangan dan hortikultura. Salah satu upaya untuk memperbaiki kondisi tersebut adalah melalui pemberian kapur pertanian atau pengapuran. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan keterampilan petani mengenai manfaat, dosis, dan teknik aplikasi kapur pertanian, sekaligus memperbaiki pH tanah melalui penerapan langsung di lahan. Metode kegiatan meliputi tahap persiapan (survei dan analisis tanah), pelaksanaan (penyuluhan, pelatihan, dan praktik lapangan), serta evaluasi (pengukuran pH tanah dan peningkatan pengetahuan peserta). Materi kegiatan mencakup konsep pH tanah, pengaruhnya terhadap pertumbuhan tanaman, jenis kapur pertanian, perhitungan dosis kapur, serta teknik aplikasi di lapangan. Hasil kegiatan menunjukkan adanya peningkatan pemahaman petani mengenai peran kapur pertanian, serta adanya perbaikan pH tanah di lahan percontohan setelah pengapuran. Dengan demikian, kegiatan pengapuran di Desa Tanjung Sari terbukti bermanfaat dalam meningkatkan kualitas tanah dan mendukung produktivitas pertanian berkelanjutan. Ke depan, diharapkan petani dapat menerapkan teknologi ini secara mandiri dan pemerintah daerah dapat memberikan dukungan melalui penyediaan kapur pertanian secara berkelanjutan.